ICT usage to enhance firms' business processes in Tanzania - Kelefa Mwantimwa (Journal of Global Entrepreneurship Research, 2019)
This study examined the usage of ICTs to enhance business processes in Tanzania. In particular, the study examined the types of ICTs deployed to enhance business processes and the processes they support, determinants of ICTs' viable usage, and barriers to their effective usage. Descriptive cross-sectional design using surveys was deployed to gather qualitative and quantitative data from 182 firms. Quantitative data were analysed with using SPSS IBM 22 to generate descriptive and inferential statistics results. Besides that, a thematic and content analysis was used to analyse qualitative data which was thereafter presented in narration form. The findings revealed that mobile phones, computers, the Internet and other network systems, and social media are perceived as important in boosting business efficiency related to material, product processing, management activities, service and marketing. The findings further disclose that financial capital has a multiplying effect on other ICTs' usage determinants such as knowledge and expertise, and ICT infrastructure investments. Regarding a firm's profile, the findings indicate that the size of a firm and its source of raw materials strongly predict its innovative usage of ICTs. The results also revealed the barriers to innovative usage of ICTs and suggest that for business processes to be meaningful, a balanced deployment of ICTs should be done with proper consideration of all enabling elements.
Keywords: 650; ICTs; Social media; Usage; Firms; Business innovation; Business processes; Tanzania